Multigroup Analysis of E-Service Quality, Satisfaction, and Loyalty in E-Grocery Services - Fadhil, Muhammad; Hati, Sri Rahayu Hijrah (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: E-Grocery is a business-to-consumer (B2C) e-Commerce with the main objective of selling groceries online. The characteristics of this service include using a digital system (application/website) and sending goods immediately (door-step delivery). Amid the widespread use of e-Grocery, this study explores the relationship between e-Service Quality, e-Satisfaction, and e-Loyalty for e-Grocery products in Indonesia. Methodology: The data collected in this study were obtained from 330 respondents who were e-grocery users in Indonesia. Results: The model was estimated using partial least squares structural modeling (PLS-SEM) and multigroup analysis bootstrapping using Jamovi and SmartPLS version 4. After conducting this research, it was found that Utilitarian and Hedonic aspects have a significant relationship with e-Service Quality, e-Service Quality has an effect on e-Satisfaction, and there is a positive relationship between e-Satisfaction and e-Loyalty. Conclusions: The findings confirm a sequential relationship between utilitarian/hedonic motivations, perceived service quality, customer satisfaction, and loyalty in the context of Indonesian e-grocery services. Sociodemographic variables moderate the strength of these relationships, suggesting the importance of customer segmentation strategies in improving service outcomes. Limitations: This study is limited to the Indonesian market and may not fully represent consumer behavior in other cultural or regional contexts. Moreover, the cross-sectional design restricts the ability to infer causality, and potential self-reporting bias may affect the reliability of the responses. Contribution: This study contributes to the literature on e-commerce and digital consumer behavior by demonstrating the mediating role of satisfaction in the e-service environment and the moderating effects of demographic characteristics.